1999
DOI: 10.1021/ed076p1242
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of a Single-Crystal X-ray Diffraction Experiment into the Undergraduate Physical Chemistry Laboratory

Abstract: Recent advances in detector technology and computing methods have made it possible to incorporate X-ray diffraction methods for routine analysis into the undergraduate chemistry curriculum. At the W. M. Keck Foundation Center for Molecular Structure (CMolS) at CSU Fullerton, we have integrated a two-week laboratory for determining crystal structures of organic molecules into the upper-level physical chemistry laboratory course. During this two-week experiment, students prepare a single-crystal sample of an org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…The introduction of aspects of crystallography into particular undergraduate courses has been reported at other institutions (4,5). The introduction of aspects of crystallography into particular undergraduate courses has been reported at other institutions (4,5).…”
Section: Step-by-step Integrationmentioning
confidence: 97%
“…The introduction of aspects of crystallography into particular undergraduate courses has been reported at other institutions (4,5). The introduction of aspects of crystallography into particular undergraduate courses has been reported at other institutions (4,5).…”
Section: Step-by-step Integrationmentioning
confidence: 97%
“…In 1956, X-ray diffraction studies were first demonstrated as a valuable technique for characterizing essential oils and their derivatives . X-ray powder diffraction data on a variety of semicarbazone carbonyl type compounds including carvone were published by Meranger et al Recently, the incorporation of single-crystal X-ray diffraction into the undergraduate chemistry curriculum has since proven itself in terms of the pedagogical value and benefits to students. Despite the obvious benefits, the technique has not been adopted widely, primarily due to the expense of installing and maintaining the instrumentation needed. This experiment could become a virtual reality in the absence of equipment (see instructor Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many physics, chemistry (Fanwick, 2007;Pett, 2010) and materials science graduate programmes also include introductory notes on crystallography (Borchardt-Ott, 2012). Some undergraduate institutions have adapted the pedagogy of hands-on research to crystallography with the use of singlecrystal desktop instruments (Crundwell et al, 1999), and many other affordable virtual (Arribas et al, 2014) and tangible resources are available as educational supporting material for a number of important concepts in crystallography (Graz ˇulis et al, 2015, and references therein). As many of these concepts require capacity for abstraction and spatial vision, many educators are taking advantage of the rise of 3D-printing technologies to develop interactive haptic environments for education.…”
Section: Introductionmentioning
confidence: 99%